Infertility and coeliac disease. Issue 3 (September 1996) - Collin, P; Vilska, S; Heinonen, P K; Hällström, O; Pikkarainen, P
Abstract : BACKGROUND: Coeliac women may suffer from gynaecological and obstetric complications. It is possible that these complications are the first symptom of coeliac disease. AIMS: To investigate the occurrence of subclinical coeliac disease in patients with infertility or recurrent miscarriages. SUBJECTS: Women of reproductive age who were attending the hospital because of either primary or secondary infertility, or two or more miscarriages. Women undergoing sterilisation served as control subjects. METHODS: The diagnostic investigation for infertility included the endocrine status, diagnostic laparoscopy, investigation of tubal patency, postcoital test, and semen analysis of the partner. Circulating antibodies against IgA class reticulin and gliadin were used in screening for coeliac disease. In positive cases, the diagnosis was confirmed by small bowel biopsy specimens. RESULTS: Four (2.7%) of 150 women in the infertility group, and none of the 150 control subjects were found to have coeliac disease (p = 0.06). All four women with coeliac disease suffered from infertility of unexplained origin. Altogether 98 women had no discoverable reason for infertility. Thus, in this subgroup the frequency of coeliac disease was 4.1% (four of 98), the difference from the control group being statistically significant (p = 0.02). None of the coeliac women had extensive malabsorption, but two had iron deficiency anaemia. One women with coeliac disease has had a normal delivery. None of the 50 women with miscarriage had coeliac disease. CONCLUSION: Patients having fertility problems may have subclinical coeliac disease, which can be detected by serological screening tests. Silent coeliac disease should be considered in the case of women with unexplained infertility.